(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we investigate a rational difference equation of higher order for the existence of nonoscillatory solutions. To prove our main results, we use an inclusion theorem stated and proved in [4]. In this way, we give an answer of an open problem formulated in [3].